Chlamydia psittaci enteric infection in an adult man: A case report - Haohui Deng; Xiaoting Liang; Shuyuan Dang; Jiuxiang Qiu (International Journal of Infectious Diseases)
Objectives: Psittacosis, a zoonotic disease caused by Chlamydia psittaci (Cps), typically manifests as respiratory symptoms following the inhalation of aerosols from infected birds. Here, we report a case of Cps causing enteric infection in an adult man. Methods: An atypical case of psittacosis was reported in a 62-year-old man who presented with initial symptoms of fever and severe diarrhea after consuming undercooked pigeon meat and offal. Results: This patient was admitted to our hospital with the main complaints of fever and severe diarrhea for 4 days and a mild dry cough for half a day, initial diagnosis and treatment for acute gastroenteritis before hospitalization were ineffective. On the fourth day of symptom onset, the patient developed a mild dry cough, and pulmonary imaging showed significant changes. Subsequently, targeted next-generation sequencing (tNGS) of bronchoalveolar lavage fluid, stool, and blood samples was positive for Cps DNA, with ompA genotype A identified in both the patient and pigeons from the source. The patient was treated with levofloxacin and doxycycline, which alleviated clinical symptoms and improved the pulmonary imaging. Conclusions: This case highlights the potential of Cps causing enteric infection and emphasizes the need to consider psittacosis in patients with fever and diarrhea, particularly with relevant epidemiological history. Early diagnosis and appropriate treatment are essential for preventing severe complications and improving clinical outcomes.